Correction: Temperature dependence of anomalous protonic and superprotonic transport properties in mixed salts based on CsH2PO4. Issue 21 (19th May 2021) - Andrio, Andreu; Hernández, S. I.; García-Alcántara, C.; del Castillo, L. F.; Compañ, Vicente; Santamaría-Holek, Iván
Abstract : Correction for 'Temperature dependence of anomalous protonic and superprotonic transport properties in mixed salts based on CsH2 PO4 ' by Andreu Andrio et al., Phys. Chem. Chem. Phys., 2019, 21, 12948–12960, DOI: ; 10.1039/C8CP07472K .